High-frequency collection of food systems data: Pilots in Rwanda and Guatemala - Manners, Rhys; Müller, Anna; Jiménez, Daniel; Martínez, Jesús David (2022)
As a part of CGIAR Research Initiative on Digital Innovation's Work Package 4, "Real-time Monitoring," digital agriculture and food systems scientists at IITA and Alliance of Bioversity International and CIAT engaged with demand partners in Rwanda and Guatemala to support their timely food security and risk management decisions using high-frequency data. Pilots were developed to collate high-frequency data on diet quality, food commodity flows, markets, and infrastructure networks and develop unprecedented insights into the dynamics of food environments. This new approach is expected to empower decision-makers with quality data, serving as a basis for early warning systems and timely interventions to address hunger and malnutrition. This report presents preliminary results achieved in 2022.